Religious’ poverty. Theology and Canon Law. Notes on 600 canon - Campo Ibáñez SJ, Miguel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
One of the contributions of the 1983 Code of Canon Law is the introduction of the so called «doctrinal canons». Canon 600 offers a regulation of the evangelical counsel of poverty in which the teaching of Vatican II and the canonical regulation, common to all Consecrated, converge. Canon 600 establishes the canonical minimum upon which, together with canon 668, Religious Institutes’ proper laws will build their regulations. An adequate understanding of the canon should include the sequela Christi —and other elements pointed out by Vatican II— and the «dependence and limitation in the use and disposition of material goods», should include theological and canonical elements. This article tries to provide a synthesis of the theological and canonical elements as a framework for the understanding of religious’ poverty.
Keywords: Evangelical counsel; Voluntary poverty; Christological element; Dependence; Limitation; Vows; Simple vows; Solemn vows